Antecedents of consumer intention to use personal health technologies: Revisiting the technology acceptance model - Çalışkan, Semra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This dissertation investigates the antecedents of consumer intention to use innovations, particularly health care innovations, from the perspective of diffusion of innovation and technology acceptance and use literature. We have witnessed substantial information technology (IT) innovations with everything from Internet of Things solutions to wearable technologies like smart watches. The possible effects of IT innovations like patient empowerment, self-health-management and health motivation make us curious about the underlying factors that lead to intention to use Personal Health Technologies (PHTs). This research contributes to the understanding of important phenomena, namely intention to use innovations, in consumer behavior context enriched with health related constructs. Besides perceived innovation attributes, contextual factors like health motivation and privacy were delineated in current study. One of the contributions of this study is investigating the mediation effects of ease of use and relative advantage over other innovation characteristics. In order to clarify the effects of individual characteristics, multi-group SEM analysis was conducted and discrepancies were discovered in the relationships. Users and potential users were compared to each other for conceiving divergence between pre adoption and post-adoption beliefs. Clusters were created with respect to values of individuals and analyzed the variations in usage intentions. Both multi-group SEM and cluster analysis contribute to generalizability of technology acceptance and use models.
Keywords: Health behavior.; Health attitudes.; Behavior modification.